How do I balance the following equation? Ca(NO3)2+KOH --> Ca(OH)2+KNO3

Expert Answers
mlsiasebs eNotes educator| Certified Educator

Usually, when we are balancing equations, we need to count the individual atoms which will certainly work in this case as well but when there are polyatomic ions that do not change between the reactants and the products, we can simplify the process.

Ca(NO3)2+KOH --> Ca(OH)2+KNO3

When we look at our equation, we see that we have 1 Ca^2+, 2 NO3-, 1 K+, and 1 OH- on the reactant side and 1 Ca^2+, 2 OH-, 1 K+ and 1 NO3- on the product side.

Placing a 2 in front of KNO3 will balance the nitrates

Ca(NO3)2+KOH --> Ca(OH)2 + 2KNO3

But now we need a 2 in front of KOH to balance the K+ ions

Ca(NO3)2+ 2KOH --> Ca(OH)2+ 2KNO3

As a result, it also gives us 2 OH- ions, so we have two of those on both sides.  Now we can go back through and check and find that we have a balanced chemical equation.

rohanlekhwani | Student

Ca(No3)2 + 2KOH ---> Ca(OH)2 + 2KNo3